Panorama das contribuições da Terminologia para a Organização do Conhecimento: uma análise das teses e dissertações no Brasil a partir da Teoria da Complexidade. - Braz, Márcia Ivo (2020)
Every science or specialty has its typical discourse permeated by its own terminology and shared by members of the community. The terms are responsible for designating concepts, which refer to meanings attributed according to that specialized context. Thus, the understanding of sciences by new members or by those who deal with different types of texts for representation purposes, such as in libraries or databases, permeates the task of building terminological instruments, such as dictionaries, glossaries and vocabularies, as well as Knowledge Organization Systems such as thesauri and ontologies. These tools depict systems that, according to the Theory of Complexity (TC), can be considered complex. TC considers that characteristics such as the observation of the nature of the whole through the study of the parts and the sum of the parts result in more than the whole itself, because it considers the richness of the interactions between the subsystems. This study aims to demonstrate the incidence of terminological approaches in theses and dissertations in graduate programs in the areas: Linguistics and Information Science of Brazil and how these works reflect characteristics of the Theory of Complexity. Specifically, our objectives were: to describe and characterize the approaches of Terminological theories: Classical, Communicative, Sociotherminology and Sociocognitive; determine the application of terminological approaches in Knowledge Organization and how this is reflected in the theoretical bases and in the use and construction of terminological tools; identify trends/ prospects for Documentary Linguistics based on theoretical findings in theses and dissertations; and to present the principles of Complexity Theory and its characteristics in relation to Terminology. The basic theory is the Complexity Theory, here considered as a model of thought and a working tool, following the statements of Larsen-Freeman (1997), Larsen-Freeman and Cameron (2008), Morin (2002; 2006; 2007; 2015), which acted as a meta-theory for the others, related to Terminology: General Theory of Terminology, founded by Wüster (1998); Communicative Theory of Terminology, proposed by Cabré (1999). The corpus was composed of eighty-three (83) scientific publications, researched in the Digital Library of Theses and Dissertations under the terms "General Theory of Terminology" and "Communicative Theory of Terminology". The comparison between TC postulates and the analyzed texts proved that both terminological approaches used for the composition of the corpus refer to complex systems. Based on this consideration, we verify the innovative character of this work in order to demonstrate that the General Theory of Terminology and the Communicative Theory of Terminology present characteristics inherent to complexity, the works that follow being their presupposed complex systems.